Green and Sustainable Software Engineering - A Systematic Mapping Study - Mourão, Brunna C.; Karita, Leila; Machado, Ivan do Carmo (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2018: Anais do XVII Simpósio Brasileiro de Qualidade de Software, 2018)
Understanding how the concepts of sustainability could be incorporated to the Software Engineering (SE) concepts has gained increased attention in the last years, particularly in terms of the Software Development Life Cycle (SDLC). Several studies have addressed the impact of sustainability in the SE practice, from a range of perspectives. This study presents a systematic mapping study that aggregates, summarizes and discusses the state-of-the-art approaches for sustainable SE practice. We analyzed 75 relevant primary studies addressing methods, processes, tools and metrics proposed to support the software development in a sustainable way. The included primary studies were selected using inclusion and exclusion criteria applied to studies published prior to 2017. They were analyzed based on a set of classification criteria, including contribution types, SDLC phases, evidence types, research types, application domains, publication venues, distribution between academia and industry and research methods. The results indicated a growing interest by the SE research community in the Green and Sustainable software domain. Besides, there is an observed need for more studies on techniques, tools and metrics covering construction, testing and maintenance. The results also point out a clear view of the SE community about the need for a better alignment between research and practice in this domain.